Relational quality: further evidence of a single higher order construct in an industrial market - Batt, Peter (Norwegian Institute of Management, 2001)
While there is some evidence for a single, higher order construct which captures satisfaction and trust, evidence of its existence in industrial markets remains scant and inconclusive. However, in the context of small, family owned businesses, where consumer behaviour and industrial purchasing behaviour overlap, a single construct may be a better predictor of a market intermediary's relational building activities. Two rival models are compared which, given the high degree of correlation between satisfaction and trust, support the existence of a single satisfaction/trust construct.